GAMBAR KARTUN SEBAGAI SUATU ALTERNATIF KOMUNIKASI INFORMASI AKUNTANSI - Melati Oktafiyani (MEDIA, 2013)
This Research aims to know the content and presentation of information impacts on the efficiency of accounting informations processing ang the effectiveness when they are presented in different forms. Specifically, this research employs an innovative research design to demonstrate the usefulness of cartoon graphics in the failed and non-failed corporations decision making context compared to accounting statements and finantial ratios (conventional presentation formats). The analysis included there aspects : Company’s Liquidity, Financial Leverage, and Profitability which is presented in accounting statements, Financial Ratios, and Cartoon Graphics. The sample of this research contain 178 students from accounting department of Dian Nuswantoro University Semarang which are taken using Judgement Sampling method and Slovin Method by grouping sample with some criterias. Data were analyzed using Descriptive Statistics and Differential Test used Kruskal Wallis Test. The cartoon graphics are shown to be processed more quickly and with no loss of accuracy, compared to accounting statements but the results show that respondents are most efficient when they classify accounting information using financial ratios compared to more means of presenting accounting information. The effectiveness of financial ratios is also in significantly evidenced in both of missclasification errors (Type I and II) when compared to other forms of accounting information presentation (cartoon graphics or accounting statements).